A model specification test for GARCH(1,1) processes - Anne Leucht; Michael H. Neumann; Jens-Peter Kreiss (University of Mannheim, Department of Economics, 2013)
We provide a consistent specification test for GARCH(1,1) models based on a test statistic of Cramér-von Mises type. Since the limit distribution of the test statistic under the null hypothesis depends on unknown quantities in a complicated manner, we propose a model-based (semiparametric)bootstrap method to approximate critical values of the test and verify its asymptotic validity. Finally, we illuminate the finite sample behavior of the test by some simulations.
urn:nbn:de:bsz:180-madoc-351076
Keywords: C12; 330; Bootstrap; Cramér-von Mises test; GARCH processes; V-statistic